Does preoperatively created right to left shunt adequately reflect hypoxemia during pneumonectomy for lung cancer? - Subotic, Dragan; Ercegovac, M.; Mandaric, D.; Herth, Felix; Andric, Lj.; Gajic, M. (Medical hypotheses, 2011)
Background - No method is currently available for preoperative approximation of the patient’s situation to the one existing during pneumonectomy in general anesthesia with alternations of single and double-lung ventilation in the lateral position. We hypothesized that a patient breathing the room air in the sitting position, with the main bronchus occluded by the inflatable catheter (aimed to predict a postpneumonectomy ventilatory function), could, at least in some aspects, simulate the intraoperative situation in certain clinical conditions discussed in the text. To evaluate the hypothesis, we used data of 15 candidates for pneumonectomy at increased risk, who underwent a spirometry with the left man bronchus occluded, as a part of the postoperative lung function prediction. Arterial blood samples (pO2, pCO2, saturation, and pH) were obtained before placement of the Fogarty catheter, than after at least 60s of normal breathing with the main bronchus occluded. Significant drop in pO2 (10.35±1.65 vs. 7.79±1.40kPa) ensued within 1min after occlusion of the main bronchus. All patients were able to perform spirometry in presence of induced hypoxemia without dyspnea that would require cessation of the procedure. These results, together with the absence of cardiac rhythm disorders, lead us to believe that they would behave in the same way during a pneumonectomy with alternations of single and double-lung ventilation. Such an assumption is based on the fact that breathing the room air is less favorable from the standpoint of oxygen delivery - the content of oxygen in the room air is smaller in the room air compared to that delivered through endotracheal tube. The practical implication of this hypothesis is that assessment of oxygenation during this procedure, additionally facilitates the preoperative risk assessment in patients undergoing pneumonectomy for lung cancer. Moreover, a slight postoperative oxygenation improvement and smaller loss in FEV1 in patients with moderate COPD, mean that COPD patients are likely to do a little bit better postoperatively than predicted.
Gesehen am 25.10.2022